Promising Practices: Building the Next Generation of School Leaders (Journal of School Administration Research and Development, 2021)
This study applies transformational leadership theory practices to examine the purposeful ways in which principals work to build the next gen- eration of teacher leaders in response to the shortage of K-12 principals. Given the impact, principals have on student development and the shortage of those applying for the principalship, the purpose of this cross-case analysis was to discover how principals build leadership capacity at their respective school sites and groom individuals for leadership roles. Further, this study explored teacher perceptions of the practices in addition to factors that facilitated or inhibited the implementation of the principals’ practices. Three school principals served as the primary participants for this research, and data were gleaned from interviews, observations, and artifacts. Findings indicated that the principals fostered leadership capacity by providing authentic administrative opportunities for teachers pursuing the administration credential. Additionally, the principals’ methods for building leadership capacity were positively perceived by the identified teacher leaders. Factors that facilitated leadership capacity development include school and district systems and structures, while factors that inhibited teachers’ development include psychological concerns. This study illuminates the need for principals to build leadership capacity at their school sites in order to purposefully prepare teacher leaders for principal succession.